2013
DOI: 10.1111/irv.12177
|View full text |Cite
|
Sign up to set email alerts
|

Influenza encephalopathy and related neuropsychiatric syndromes

Abstract: Influenza is occasionally complicated by CNS disorders, in particular impairment of consciousness. Severe disorders encompass multiple, distinct syndromes manifesting acute encephalopathy, whereas mild disorders represent multiple, ill‐defined neuropsychiatric syndromes. Acute encephalopathy is manifested with seizures and coma, with or without multi‐organ involvement. The outcome varies from death or neurologic sequelae to recovery and differs among syndromes. Transient neuropsychiatric disorders are manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 36 publications
1
44
0
2
Order By: Relevance
“…Note that the detection of influenza virus from CSF is not required for a diagnosis of IAE in the Japanese guidelines because it has been shown that the influenza virus and inflammatory cells are not always detectable in the CSF of such patients, but they must have detectable influenza virus in their respiratory tract, and no other causes were found for this presentation [22•, 2527]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
“…Note that the detection of influenza virus from CSF is not required for a diagnosis of IAE in the Japanese guidelines because it has been shown that the influenza virus and inflammatory cells are not always detectable in the CSF of such patients, but they must have detectable influenza virus in their respiratory tract, and no other causes were found for this presentation [22•, 2527]. …”
Section: National Influenza Surveillancementioning
confidence: 99%
“…The fact that different infectious agents can produce a similar phenotype suggests that host factors, such as genetic variation in the adenosine A2A receptor (ADORA2A) or carnitine palmitoyl transferase II polymorphisms, significantly influence disease progression …”
Section: Discussionmentioning
confidence: 99%
“…The fact that different infectious agents can produce a similar phenotype suggests that host factors, such as genetic variation in the adenosine A2A receptor (ADORA2A) or carnitine palmitoyl transferase II polymorphisms, significantly influence disease progression. [23][24][25] The underlying biological mechanisms in RSV-associated encephalopathy still require clarification. The absence of CSF pleocytosis in all but one of the present patients with brain lesions excludes encephalitis as the common cause.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criterion for encephalitis and encephalopathy was “a disturbance of consciousness lasting more than 24 h”, which met the criteria for influenza‐associated encephalopathy in the Japanese guidelines . All febrile convulsion patients woke up within 24 h after admission and had no neurological sequelae at discharge.…”
Section: Methodsmentioning
confidence: 99%
“…All encephalopathy group patients had disturbance of consciousness >10 on the Japan coma scale, but not all of these patients had MRI. The classification of encephalopathy depends on the classification by Mizuguchi, which is prevalent in Japan.…”
Section: Methodsmentioning
confidence: 99%